The Role of Cybersecurity in Defense Technology Innovation: A System Thinking Approach to Deal with Cyber Threats in The Era of Industrial Revolution 4.0 - Agus Juniawan Khairi; Sri Yanto; Aries Sudiarso (Jurnal Multidisiplin Madani, 2024)
The world has entered the era of the Industrial Revolution 4.0, where defense technology has undergone a transformation to digital technology, thus presenting new problems in the form of cyber threats that develop dynamically following technological developments. The threat of cyber-attacks can be in the form of theft of confidential data or sabotage of military or public facilities. The all-digital defense technology innovation process is an advantage in the aspect of cyber security, where military equipment is interconnected to facilitate and increase the efficiency of operations in the field. This article discusses the strategic role of cybersecurity in supporting defense technology innovation, using a system thinking approach, enabling a more holistic understanding of the interaction between components in the defense technology system, as well as its impact on national cybersecurity. Using a literature review and case study analysis, this article explores in depth the incidence of cyberattacks, and through a system thinking approach it identifies, analyzes and mitigates the risks arising from cyber threats. In addition, this article also discusses the importance of cybersecurity integration in defense technology innovation to ensure system resilience in the face of various forms of cyberattacks. It is hoped that this method can increase the durability of defense technology by focusing on strategic advantages in global competition